2016
DOI: 10.1103/physrevb.93.144414
|View full text |Cite
|
Sign up to set email alerts
|

Disorder-promotedC4-symmetric magnetic order in iron-based superconductors

Abstract: In most iron-based superconductors, the transition to the magnetically ordered state is closely linked to a lowering of structural symmetry from tetragonal (C4) to orthorhombic (C2). However, recently, a regime of C4-symmetric magnetic order has been reported in certain hole-doped ironbased superconductors. This novel magnetic ground state can be understood as a double-Q spin density wave characterized by two order parameters M1 and M2 related to each of the two Q vectors. Depending on the relative orientation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
82
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(88 citation statements)
references
References 52 publications
6
82
0
Order By: Relevance
“…Since then, theory has shown that impurity scattering can play a significant role in the stabilization of the C 4 phase. 17 In their work, Hoyer et al show that intraband electron scattering due to crystallographic defects stabilize the C 4 phase at lower doping concentrationsat the begining of the C 4 dome. However, no such effect is found on the higher doped side of the dome in agreement with our observation of mixed phase samples at the onset of C 4 in composition but not at higher consentrations.…”
Section: W E I G H T E D P H a S E F R A C T I O Nmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, theory has shown that impurity scattering can play a significant role in the stabilization of the C 4 phase. 17 In their work, Hoyer et al show that intraband electron scattering due to crystallographic defects stabilize the C 4 phase at lower doping concentrationsat the begining of the C 4 dome. However, no such effect is found on the higher doped side of the dome in agreement with our observation of mixed phase samples at the onset of C 4 in composition but not at higher consentrations.…”
Section: W E I G H T E D P H a S E F R A C T I O Nmentioning
confidence: 99%
“…Consequently, it has become the focus of many recent first principle reports to reveal what parameters are causing the sudden reordering of the single-Q C 2 structure into this novel double-Q structure and how this new phase hosts superconductivity. 12,[15][16][17][18][19] Currently, several different proposed models predict the observed C 4 but they do so through different mechanisms which range from expanded itinerant mean field models to impurity scattering stabilization to spin-orbit coupling driven spin anisotropies. 15,17,18 The different models invoke varying assumptions about the underlying physics in these materials and necessarily predict different, sometimes subtlety so, manifestations of the C 4 phase.…”
Section: Introductionmentioning
confidence: 99%
“…This C 4 magnetic state is characterized by biaxial magnetic orders [29][30][31][32][33], and the corresponding spin operator is given by S(r) = M X e iQX ·r + M Y e iQY ·r [33,34]. It has been suggested that this double-Q magnetic state has two possible realizations [29][30][31][32][33]35]: a charge-spin density wave (CSDW) in which M X and M Y are collinear; a spin-vortex crystal (SVC) in which M X and M Y are orthogonal.…”
Section: Introductionmentioning
confidence: 99%
“…Since the largest value of T c of FeSCs is observed at the proximity of tetragonal C 4 magnetic order [22,26], there might exist a quantum critical point (QCP) at certain doping x c in the superconducting (SC) dome [33]. After its discovery, the double-Q structured C 4 SDW state has stimulated a variety of experimental [21,22,[24][25][26][27] and theoretical works [29][30][31][32][33][34][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation